Do external grants to district governments discourage own-revenue generation?: A look at local public finance dynamics in Ghana - Mogues, Tewodaj; Benin, Samuel; Cudjoe, Godsway (International Food Policy Research Institute, 2009)
Decentralization is expected to lead to greater efficiency in the allocation of public resources, as subnational governments are said to have better information than central government about the needs for and requirements of public services in their jurisdictions, especially in agricultural and rural areas, where information about rural residents' priorities is more limited. This purported benefit of decentralization rests strongly on the assumption that local governments can in fact exercise fiscal discretion to allocate resources. However, local government budgets are commonly dominated by intergovernmental and external transfers, which are often tied to specific investments, and these at times may not match local government priorities. Thus, local governments' fiscal autonomy may ultimately depend on their ability to generate sufficient revenue internally. Panel data on district governments' public finances in Ghana are used to examine the impact of the flow and size of external transfers on districts' internally generated revenues. The evidence suggests that external transfers crowd out local governments' own revenues, which could potentially result in the loss of equity and efficiency gains associated with decentralization. This result points to the need for a careful review of Ghana's fiscal transfer mechanisms in light of the central government's goal of encouraging districts to contribute to rural development through effective local public spending and public service provision.